Application of the Servqual Method and the Kano Model as Measurement of Service Quality towards Customer Satisfaction in Senyum Media Bondowoso - Firrizqi Satria Wibawa; Nurul Qomariah; Yusron Rozzaid (Garuda Prestasi Nusantara Consulting, 2021)
This research aims to analyze the level of customer satisfaction to services and explain the factors that must be prioritized in order to meet consumer expectations in Senyum Media Bondowoso. The method used is quantitative research with the Servqual method and the Kano model. The population of this research is all the customers of the Senyum Media Bondowoso store and the samples used are 150 samples using the Purposive Sampling technique. The results of the research show that the quality of service in CV. Senyumindo Mediatama Bondowoso is not in accordance with what is desired by customers, because the calculation is carried out using the Service Quality method, the results obtained are the average value of service quality, the average value of service quality for all dimensions of service quality is -4,967. On the other hand, for the Kano category is in the Indifferent category, which means that the attributes that are in the category of less attention by consumers, therefore the existence of these attributes does not affect the decrease or increase in the level of satisfaction of consumers. This category has no effect on consumer satisfaction with functional or dysfunctional services and goods.